A missed medial humeral epicondyle fracture with incarcerated fragment in the elbow joint and ulnar nerve palsy: A rare case report. Issue 10 (25th October 2021) - Das, Subhash Kumar; Bohara, Sujan; Bhandari, Ravi; Sinha, Ritesh; Das, Bikash; Karki, Samikshya
Abstract: Medial epicondyle fracture associated with incarcerated intra‐articular fragment and ulnar nerve palsy is uncommon and frequently missed. We report a case of 13‐year‐old boy with incarcerated medial epicondyle fracture fragment in ulnohumeral joint and ulnar nerve palsy, which was managed successfully by open reduction internal fixation and ulnar nerve transposition. Abstract : Medial epicondyle fracture associated with incarcerated intra‐articular fragment and ulnar nerve palsy is uncommon and frequently missed. We report a case of 13‐year‐old boy with incarcerated medial epicondyle fracture fragment in ulnohumeral joint and ulnar nerve palsy, which was managed successfully by open reduction internal fixation and ulnar nerve transposition.